Transfer Phenomena of Nanoliposomes by Live Imaging of Primary Cultures of Cortical Neurons - Elodie Passeri; Philippe Bun; Kamil Elkhoury; Michel Linder; Catherine Malaplate; Frances T. Yen; Elmira Arab-Tehrany (MDPI AG, 2022)
Soft nanoparticles, and in particular, nanoliposomes (NL), have attracted increasing interest for their use in food, nutraceuticals, and in particular, in pharmaceutics for drug delivery. Recent data using salmon lecithin NL suggest that these NL, rich in omega-3 (n-3) fatty acids, can improve the bioavailability and transport of molecules through the blood brain barrier (BBB) to target the brain for the prevention and treatment of neurodegenerative diseases. The objective of this study was to characterize the physicochemical properties and analyze the transfer phenomena of salmon lecithin NL over time in neurons to better understand the behavior of NL in an intracellular environment. To test this, primary cultures of cortical neurons from rat embryos were incubated with salmon lecithin NL from day 3 after cell culture, for up to 104 h. The physicochemical properties of NL such as size, speed, morphology and the diffusion coefficient in the live cultures, were studied over time. Image analysis of cell morphology showed dendritic growth and neuronal arborization after 48 h of exposure to NL, for up to 104 h. Results showed an NL stability in size, speed and diffusion coefficient over time, with a peak at 48 h, and then a return to baseline value at the end of incubation. The average speed and diffusion coefficient achieved provided important information on the mode of entry of NL into neurons, and on the slow diffusion rate of NL into the cells. Analysis of videos from 2 h to 104 h showed that significant levels of NL were already internalized by neurons after 3 h incubation. NL appearance and intracellular distribution indicated that they were packed in intracellular compartments similar to endocytic vesicles, suggesting internalization by an active endocytic-like process. The results obtained here demonstrate internalization of NL by cortical neurons by an active endocytic-like process, and suggest the potential use of NL for time-release of therapeutics aimed towards prevention or treatment of neurodegenerative diseases.